(untitled) (CIPEEX, 2022)
PSYCHIATRIC DISORDERS ARE ALTERATIONS IN THE FUNCTIONING OF THE MIND THAT REFLECT ON THE PERFORMANCE AND QUALITY OF LIFE OF INDIVIDUALS. IN THE CASE OF WOMEN, ADDING THESE DISTURBANCES TO THE GESTATIONAL MOMENT, THESE DISORDERS CAN WORSEN, DUE TO THE INTENSE PHYSICAL AND PSYCHOLOGICAL CHANGES THAT OCCUR DURING THIS PERIOD. THUS, AS A RESULT OF THE GROWING USE OF PSYCHOTROPIC DRUGS AND THEIR IMPACTS, THE PRESENT RESEARCH PRESENTED THE FOLLOWING GUIDING QUESTION: €ŒWHAT ARE THE REPERCUSSIONS THAT THE USE OF PSYCHOTROPIC DRUGS CAN GENERATE DURING PREGNANCY, IN THE NEWBORN AND IN EARLY CHILDHOOD. THIS IS AN INTEGRATIVE LITERATURE REVIEW WITH A SEARCH FOR ORIGINAL ARTICLES US NATIONAL LIBRARY OF MEDICINE (PUBMED) AND VIRTUAL HEALTH LIBRARY (BVS), WHICH ALLOWED DIVING AND DEEPENING INTO THE FOLLOWING CATEGORIES: PREGNANCY, NEONATES AND EARLY CHILDHOOD. WITH REGARD TO PREGNANCY AND THE USE OF PSYCHOTROPIC DRUGS, THERE IS A GREATER RISK OF DEVELOPING GESTATIONAL DIABETES MELLITUS (GDM) AND MUSCULOSKELETAL MALFORMATIONS. REGARDING THE IMPACTS ON THE NEWBORN, THERE WAS AN INTRINSIC RELATIONSHIP BETWEEN THE USE OF CRACK AND COCAINE AND THE INCREASE IN THE PREVALENCE OF NEWBORNS CLASSIFIED AS SMALL FOR GESTATIONAL AGE (SGA). IN ADDITION, PREMATURITY, FROM MODERATE TO LATE, WAS INCREASED FOR WOMEN TREATED WITH ANTIPSYCHOTICS. ALREADY IN EARLY CHILDHOOD, THERE WAS NO SIGNIFICANT INCREASE IN THE RISK OF DEVELOPING AUTISM SPECTRUM DISORDER, ATTENTION DEFICIT AND HYPERACTIVITY DISORDER. THEREFORE, THE FINDINGS ALLOWED INFERRING THAT THERE WERE CLINICAL REPERCUSSIONS IN THE 3 LISTED CATEGORIES. THUS, IT IS EXTREMELY IMPORTANT TO WEIGH RISKS AND BENEFITS IN THE USE OF PSYCHOTROPIC DRUGS IN THE PRENATAL AND POSTPARTUM PERIOD, SINCE FETAL EXPOSURE IS ASSOCIATED WITH A HIGHER RISK OF NEONATAL MORBIDITY.